Shock Absorbers or Transmitters? : The Role of Foreign Banks during COVID-19 - Yao, Weijia (IMF Working Papers; Working Paper, 2022)
This paper studies whether bank ownership influenced lending behavior during the COVID-19 shock. It finds that, similar to previous episodes of financial distress, foreign banks appear to have played a shock-transmitting role, as there was a sharp slowdown in lending by foreign banks' affiliates relative to domestic banks. However, given the uniqueness of the COVID-19 shock and the impact of lockdowns on economic activity, foreign banks were found to lend at a higher rate than domestic banks once the stringency of mobility restrictions is accounted for, with their lending portfolio concentrated more in the corporate sector. Results also suggest that the difference in lending rates between foreign and domestic banks could be explained by the heterogeneous effects of policy measures in response to the pandemic. In jurisdictions with more stringent mobility restrictions, policy interventions actually encouraged higher lending by foreign banks. These findings suggest that foreign bank presence may have acted as a shock absorber in jurisdictions where economic activity was most affected by the pandemic.